Contribution of Constituents in Rosemary-Magnolia Compound Essential Oil to Antibacterial, Antioxidant and Cytotoxicity Bioactivities Revealed by Grey Correlation Analysis - Song, Y.; Zhang, P.; Jiao, Q.; Gu, R.; Qu, L.; Huang, S.; Zhang, D.
The compound of essential oils (EOs)is a key approach to achieving the superimposed efficacy of plant EOs. In this article, grey correlation analysis was applied for the first time to explore the compound ratios and contribution between constituents and the bioactivity of the compound EOs. There were 12 active constituents shared in rosemary and magnolia EOs prepared by negative pressure distillation. With different proportions, these two EOs were blended and analyzed for the antioxidant, bacteriostatic and antitumor effects. According to the results of the inhibition circle, minimum bactericidal and inhibitory concentration, the most obvious inhibition effect of the compound EOs on different strains of bacteria was shown in Staphylococcus aureus. The results of antioxidant test showed that single EO from rosemary had the best antioxidant effect, and its EO content was directly proportional to the antioxidant effect. The cytotoxicity results showed that, there was a significant difference in the lethality of the compound EOs between tumor cells Mcf-7 (human breast cancer cells)and SGC-7901 cells (human gastric cancer cells). Furthermore, single EO from magnolia had an obvious inhibitory effect on the growth of Mcf-7 cells and SGC-7901 cells, and the cell lethality rate was as high as 95.19 percent and 97.96 percent, respectively. As the results of grey correlation analysis, the constituents with the maximal correlation of inhibitory effects on bacteria were as follows: S. aureus - Terpinolene (0.893), E. coli - Eucalyptol (0.901), B. subtilis - ?-Pinene (0.823), B. cereus - Terpinolene (0.913)and Salmonella - ?-Phellandrene (0.855). For the ABTS and DPPH scavenging effects, the constituents with the maximal correlation were (-)-Camphor (0.860)and ?-Pinene (0.780), respectively. In terms of the effects of the active constituents of compound EOs on the inhibitory activities of tumor cells Mcf-7 and SGC-7901, the three active constituents of ?-Terpinene, (R)-(+)-?-Citronellol and (-)-Camphor were in the top three, and their correlation were Mcf-7 (0.833, 0.820, 0.795)and SGC-7901 (0.797, 0.766, 0.740). Our study determined the contribution degree of active constituents in the antibacterial, antioxidant, and antitumor bioactivities of rosemary-magnolia compound EOs, and also provided new insights for the research of EOs combination formulations.
Keywords: ANTIBACTERIAL; ANTIOXIDANT; COMPOUND ESSENTIAL OILS; CYTOTOXICITY; GREY CORRELATION ANALYSIS